Aligning Universities Requirements of Indigenous Academics with the Tools used to Evaluate Scholarly Performance and Grant Tenure and Promotion - Louie, Dustin William (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
The aim of this paper is to challenge the discrepancy between candidate requirements in job postings for Indigenous scholars and their recognition in the tenure-track stream. For the purposes of this article, I conducted a scan of 11 academic positions for Indigenous scholars advertised in Canada from 2017 to 2019. One-hundred percent of the postings included an expectation for the candidate to hold Indigenous Knowledges and connections to Indigenous communities. Through the examination of seminal Indigenous scholars I unearth the capacities required to hold, maintain, and renew Indigenous Knowledges and connections to community, while simultaneously showing that none of these capacities are recognized within funding allowances, workload allotments, or tenure and promotion committees. Finally, practical recommendations are offered to post-secondary institutions to provide a supportive environment for Indigenous scholars to enjoy success while holding Indigenous Knowledges and community connections in a good way. Keywords: Indigenous education; decolonizing post-secondary education; anti-oppressive education